2017
DOI: 10.7554/elife.29173
|View full text |Cite
|
Sign up to set email alerts
|

Neural stem cells induce the formation of their physical niche during organogenesis

Abstract: Most organs rely on stem cells to maintain homeostasis during post-embryonic life. Typically, stem cells of independent lineages work coordinately within mature organs to ensure proper ratios of cell types. Little is known, however, on how these different stem cells locate to forming organs during development. Here we show that neuromasts of the posterior lateral line in medaka are composed of two independent life-long lineages with different embryonic origins. Clonal analysis and 4D imaging revealed a hierarc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 57 publications
(102 reference statements)
1
22
0
Order By: Relevance
“…Importantly, as dying hair cells are continuously replaced during homeostasis, our analyses also characterized support cells as they differentiated into hair cells. Even though lineage relationships cannot be inferred from scRNA-Seq data alone, the results of our pseudotime and cell classification delineate lineages that have been experimentally confirmed by time lapse and lineage tracing analyses (Romero-Carvajal et al, 2015; Seleit et al, 2017; Viader-Llargués et al, 2018; Figure 2E–F and Figure 3A–C and L–M). The majority of hair cells originate from central support cells without bias to any of the poles (Figure 3M, clusters 7, 9, 8, 14 and 4), whereas amplifying divisions are strongly biased towards the D/V poles and occur in the periphery adjacent to mantle cells (Figure 3M, clusters 10 and 3).…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Importantly, as dying hair cells are continuously replaced during homeostasis, our analyses also characterized support cells as they differentiated into hair cells. Even though lineage relationships cannot be inferred from scRNA-Seq data alone, the results of our pseudotime and cell classification delineate lineages that have been experimentally confirmed by time lapse and lineage tracing analyses (Romero-Carvajal et al, 2015; Seleit et al, 2017; Viader-Llargués et al, 2018; Figure 2E–F and Figure 3A–C and L–M). The majority of hair cells originate from central support cells without bias to any of the poles (Figure 3M, clusters 7, 9, 8, 14 and 4), whereas amplifying divisions are strongly biased towards the D/V poles and occur in the periphery adjacent to mantle cells (Figure 3M, clusters 10 and 3).…”
Section: Discussionsupporting
confidence: 52%
“…Mantle cells are the outermost cells in a neuromast and sit immediately adjacent to amplifying support cells (Figures 1B,M,N,R–U). Lineage tracing of mantle cells in medaka revealed that mantle cells give rise to support and hair cells and constitute long term stem cells (Seleit et al, 2017). In addition, they give rise to postembryonic neuromasts during development and restore neuromasts on regenerating tail tips (Dufourcq et al, 2006; Ghysen and Dambly-Chaudière, 2007; Jones and Corwin, 1993; Ledent, 2002; Wada et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, further application of this integrated approach and new transgenic markers may reveal uncharacterized cells in the neuromast. This may be expected given recent work that showed the existence of a new cell class in neuromasts of medaka fish ( Seleit et al, 2017 ). It is technically challenging to consistently maintain fewer than 4 cells in toto without eliminating the entire neuromast.…”
Section: Resultsmentioning
confidence: 73%
“…The HC progenitors are located in the center of the neuromast, whereas the stem cells are located at the anterior and posterior poles [ 79 ]. Strikingly, the surrounding mantle cells act as long-term quiescent stem cells for the neuromast, in addition to providing specific niche signals to maintain the self-renewing stem cells [ 80 ]. Analysis of the regulation of neuromast regeneration reveals spatially segregated, parallel signaling pathways to control proliferation, differentiation, and organ size.…”
Section: Spontaneous Cochlear Regenerationmentioning
confidence: 99%